A Systematic Review of ICU and Non-ICU Clinical Pharmacy Services Using Telepharmacy. Issue 12 (December 2018) - Strnad, Kyle; Shoulders, Bethany R.; Smithburger, Pamela L.; Kane-Gill, Sandra L.
Objective: To assess the impact of telepharmacy services in the acute care setting.Data Sources: EMBase, MEDLINE, and SCOPUS database searches were performed through April 2018.Study Selection and Data Extraction: PRISMA guidelines were applied for this systematic review. All English-language studies meeting the criteria of the following population, intervention, comparison, and outcome question were included: What impact does the provision of inpatient clinical pharmacy services delivered via telemedicine have on patient outcomes compared with standard of care?Data Synthesis: A total of 11 studies were identified for the acute care setting, including 3 for critically ill patients. All studies demonstrated a positive impact on patient outcomes, nursing satisfaction, and disease management. Varying modes of telepharmacy technology were used, such as remote access to electronic medical records, faxing or scanning documents, pictures or webcams. For communication purposes, telepharmacists used email or electronic communication, facsimile, video review, or telephone to speak directly with hospital personnel and patients.Relevance to Patient Care and Clinical Practice: Inpatient telepharmacy is feasible and should be leveraged to further enhance patient care by complementing existing service models.Conclusions: Telepharmacy services enhanced patient outcomes, improved nursing satisfaction, and expanded services within inpatient settings. Similar technologies were leveraged in non–intensive care units (ICUs) and ICUs, but the goals of telepharmacy appeared to differ. ICUs focused on an expansion of services in the ICU and non-ICUs addressed improved patient outreach in rural areas.